Kepercayaan Masyarakat Terhadap Ritual Mitoni Ditinjau dari Aqidah Islam: (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2020)
This article is entitled Public Trust in Mitoni Rituals Viewed From Islamic Aqidah (Study in Rejosari Village, Muara Sugihan District, Banyuasin District) Mitoni ritual is a ritual that is held in the seventh month of pregnancy of the first child. The purpose of the mitoni ritual is so that the baby is in the womb. and pregnant women always get safety and smoothness until the time of delivery. This type of research is field research. There are two types of data in this research, namely primary data and secondary data. The primary data of this study are the main data, namely the community. Rejosari Village, which includes the village head, village traditional leaders, religious leaders and the Rejosari village community. Meanwhile, secondary data is a variety of literature and documents related to this research such as books, internet and thesis. From the results of the author's analysis, it can be concluded that the people of Rejosari Village, Muara Sugihan Kebup District aten Banyuasin, still strongly believes in the mitoni ritual. This is because the people of Rejosari village still believe that the mitoni ritual is a sacred ritual, so they are afraid to leave or ignore the ritual, because unwanted things will happen, such as death. Meanwhile, in the review of Islamic Aqidah, there is actually no prohibition against implementing mitoni, because there is not a single verse of the Al-Qur'an and Hadith that prohibits mitoni.